2021
DOI: 10.3389/fimmu.2021.631235
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial-Immune Crosstalk in Pulmonary Fibrosis

Abstract: Interactions between the lung epithelium and the immune system involve a tight regulation to prevent inappropriate reactions and have been connected to several pulmonary diseases. Although the distal lung epithelium and local immunity have been implicated in the pathogenesis and disease course of idiopathic pulmonary fibrosis (IPF), consequences of their abnormal interplay remain less well known. Recent data suggests a two-way process, as illustrated by the influence of epithelial-derived periplakin on the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 217 publications
(260 reference statements)
0
14
0
Order By: Relevance
“…In vivo, experimental models have shown that several mucins (MUC1, MUC5b, MUC4) can influence EMT through different mechanisms, such as promoting fibroblast proliferation and migration while exerting also anti-apoptotic activities [ 52 , 53 , 54 , 55 ]. Indeed, their genetic and pharmacologic modulation was found to protect bleomycin-treated mice by interfering with TGF-β1-induced EMT or myofibroblast differentiation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, experimental models have shown that several mucins (MUC1, MUC5b, MUC4) can influence EMT through different mechanisms, such as promoting fibroblast proliferation and migration while exerting also anti-apoptotic activities [ 52 , 53 , 54 , 55 ]. Indeed, their genetic and pharmacologic modulation was found to protect bleomycin-treated mice by interfering with TGF-β1-induced EMT or myofibroblast differentiation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory epithelium plays a pivotal role in disease pathogenesis and progression [ 2 , 3 ]. In addition, for the treatment of lung diseases as well as other organ diseases, the respiratory epithelium, with its size of 100 square meters, represents a promising approach for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of innate immunity, including monocyte, macrophage, dendritic cell and mast cell, is responsible for progression and a poor prognosis of IPF( Scott, Quinn et al, 2019 ; Overed-Sayer, Miranda et al, 2020 ; Bocchino, Zanotta et al, 2021 ; Mattoo and Pillai 2021 ; Shenderov, Collins et al, 2021 ; van Geffen, Deißler et al, 2021 ). Th1/Th2 imbalance also contributes to aggravation of IPF, but which of them plays a dominant role remains controversial ( Desai, Winkler et al, 2018 ; Planté-Bordeneuve, Pilette et al, 2021 ; Shenderov, Collins et al, 2021 ). Th17 cell and Treg cell have been proven positively associated with the development of IPF ( Shenderov, Collins et al, 2021 ; van Geffen, Deißler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%